Evaluating IPv6 Support in Kubernetes - Kjorveziroski, Vojdan; Mishev, Anastas; Filiposka, Sonja (IEEE, 2021)
Kubernetes is one of the most popular container orchestrators today, but IPv4 address scarcity and the lucrative reseller market introduce problems for cluster administrators who would like to deploy publicly available applications, without resorting to NAT. We discuss the extent of IPv6 support in recent versions of Kubernetes and offer solutions for IPv6 dual-stack implementation. We also provide a reference dual-stack IPv6 Kubernetes network architecture that can be employed in existing or new clusters.
Keywords: cloud computing, IPv6, Kubernetes, containers, overlay networks